2017
DOI: 10.18632/oncotarget.18488
|View full text |Cite
|
Sign up to set email alerts
|

p53-independent p21 induction by MELK inhibition

Abstract: MELK play critical roles in human carcinogenesis through activation of cell proliferation, inhibition of apoptosis and maintenance of stemness. Therefore, MELK is a promising therapeutic target for a wide range of cancers. Although p21 is a well-known p53-downstream gene, we found that treatment with a potent MELK inhibitor, OTS167, could induce p21 protein expression in cancer cell lines harboring loss-of-function TP53 mutations. We also confirmed that MELK knockdown by siRNA induced the p21 expression in p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 23 publications
3
30
0
Order By: Relevance
“…In addition, in accordance with bioinformatics analyses of GSE13507, MELK was involved in the cell cycle, G1/S transition of the mitotic cell cycle, DNA repair and replication, which was similar to previous reports 6,26,33,[39][40][41][42][43]. A, The expression of MELK was up-regulated at transcription level with MELK plasmid; it was down-regulated by OTSSP167.…”
supporting
confidence: 90%
“…In addition, in accordance with bioinformatics analyses of GSE13507, MELK was involved in the cell cycle, G1/S transition of the mitotic cell cycle, DNA repair and replication, which was similar to previous reports 6,26,33,[39][40][41][42][43]. A, The expression of MELK was up-regulated at transcription level with MELK plasmid; it was down-regulated by OTSSP167.…”
supporting
confidence: 90%
“…Another two studies reported that MELK expression is associated with tumor cell mitosis and promotes tumor cell proliferation . MELK also plays an important role in the P53‐P21 apoptotic pathway . Based on the above findings, we used different concentrations of inhibitor OTSSP167 and siRNA knockdown MELK to detect cervical cell proliferation, colony formation ability, and apoptosis‐related proteins P53, cleaved caspase‐3.…”
Section: Discussionmentioning
confidence: 93%
“…Some of the isoforms could act similar to p53 protein and play a redundant role ( Pflaum, Schlosser & Müller, 2014 ). In addition, there is plenty of other evidence to suggest that p53 pathway-related genes could be regulated in a p53-independent manner, mediated by C/EBP, Rb, Oct1/NF-Y, or MELK respectively ( Chinery et al, 1997 ; Sun et al, 1998 ; Hirose et al, 2003 ; Matsuda et al, 2017 ). It was shown previously that cellular ROS up-regulated the expression of p21 in a p53-independent manner ( Russo et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%